STRATEGIES FOR HELPING CHILDREN UNDERSTAND MATHEMATICAL CONCEPTS - Edwin-Ezeoka, Cynthia A.; Ekweozor, Edith C.; Bello, Usman (Journal of Early Childhood and Primary Education, 2020)
This study investigated the strategies for promoting primary school pupils’ understanding of mathematical concepts in Onitsha south local government Area, Anambra state. A descriptive survey design was adopted. Two research questions guided the study. The population consists of 1,105 primary school teachers with a sample of 100 teachers drawn using simple random sampling technique. A 20 item Questionnaire titled “Strategies for Promoting Primary School Pupils’ Understanding of Mathematical Concepts Questionnaire (SPPSPUMCQ) was used to collect the data. The instrument was validated by 3 research experts. The data collected were analyzed using mean. A gross reliability coefficient of 0.75 was obtained using Cronbach-Alpha method. Result showed that lack of adequate textbooks, instructional materials and parental support are the factors that hinder pupils’ understanding of mathematical concepts. The study therefore recommended among others that Mathematics should be taught by specialized teachers, Parents should endeavour to give full support to pupils’ mathematics learning, adequate textbooks and instructional materials should be provided for the pupils’ teaching and learning of mathematics.
Keywords: Strategies; mathematics; mathematical concepts; primary education